Chlorophyll fluorescence intensity, photosynthetic yield and flowering in fig fruit trees as affected by phloem stress - Hossain, A.B.M.S.; Salleh, A.; Mekhled, M.A.; Al-Saif, A.M. (Scientific Issues Natl Centre Agrarian Sciences, 2010)
HOSSAIN, A. B. M. S., A. SALLEH, M. A. MEKHLED and A. M. Al-SAIF, 2010. Chlorophyll fluorescence intensity, photosynthetic yield and flowering in fig fruit trees as affected by phloem stress. Bulg. J. Agric. Sc., 16: 547-552 Chlorophyll fluorescence intensity, photosynthetic yield in leaves and flowering of fig trees (Ficus carica L.) as affected by phloemic stress (represented by partial bark ring) were studied. The treatments were un-ringed, I-shape partial ring (I-SPR), X-shape partial ring (X-SPR) and S-shape partial ring (S-SPR). The greater bark thickness (width) was found in I SPR treated branch than other treated branches. Branch circumference of all three types of treatment showed higher value in upper ring than in lower ring. The maximum SPAD value was observed in control branch earlier after treatment whereas the maximum value was found in S-SPR treated branch later. Besides, the percent flower bud and fruit set were greater in S-SPR treated trees than other treated branches. The flower bud and fruit set were higher in treated branches than in control. Chlorophyll fluorescence intensity was found similar upward trends with some fluctuations in case of all treatments. The intensity was higher in control and I-SPR treated branches than in other treatments. Fo (lower fluorescence), Fm (higher fluorescence), Fp (Intermediate fluorescence) were highest in leaves of control, I-SPR and X-SPR treated branches. However, X-SPR treatment represented the maximum optimum quantum yield [(Photosynthetic yield (Fv/Fm)]. Resulting, the study represents that phloemic stress (I-SPR, X-SPR & S-SPR), can be applied for the dwarfing physiological growth and early flowering of fig tree and the most effective one was S-SPR.